Third-Generation Balloon and Self-Expandable Valves for Aortic Stenosis in Large and Extra-Large Aortic Annuli From the TAVR-LARGE Registry. (August 2020) - Armijo, Germán; Tang, Gilbert H.L.; Kooistra, Nynke; Ferreira-Neto, Alfredo Nunes; Toggweiler, Stefan; Amat-Santos, Ignacio J.; Keller, Lukas S.; Urena, Marina; Ahmad, Hasan; Tafur Soto, Jose; Muñoz-Garcia, Erika; Regueiro, Ander; et al.
Abstract : Background: Currently, 2 third-generation transcatheter valves, 29-mm Sapien-3 and 34-mm Evolut-R (ER), are indicated for large sized aortic annuli. We analyzed short and 1-year performance of these valves in patients with large (area ≥575 mm 2 or perimeter ≥85 mm) and extra-large (≥683 mm 2 or ≥94.2 mm) aortic annuli undergoing transcatheter aortic valve replacement. Methods: A total of 833 patients across 12 centers with symptomatic aortic stenosis and large aortic annuli underwent transcatheter aortic valve replacement with 29-mm Sapien-3 (n=640) or 34-mm ER (n=193). Clinical, anatomic, and procedural characteristics were collected, and Valve Academic Research Consortium-2 outcomes were reported. Results: Median aortic annulus area and perimeter were 617 mm 2 (591–657) and 89.1 mm (87.0–92.1), respectively (704 mm 2 [689–743] and 96.0 mm [94.5–97.9] in the subgroup of 124 patients with extra-large annuli). Overall device success was 94.3% (Sapien-3, 95.8% and ER, 89.3%; P =0.001), with a higher rate of significant paravalvular leak ( P =0.004), second valve implantation ( P =0.013), and valve embolization ( P =0.009) in the ER group. Thirty-day and 1-year mortality was 2.4% and 9.2%, respectively, without differences between groups. Valve hemodynamics were excellent (mean gradient, 8.8±3.6 mm Hg; 3.3% rate of moderate-severe paravalvular leak) in the extra-large annulus, without differences compared with the large annulus group. Conclusions: In patients with large and extra-large aortic annuli, transcatheter aortic valve replacement using 29-mm Sapien-3 and 34-mm ER is safe and feasible. Observed differences in clinical outcomes and hemodynamic performance may guide valve choice in this cohort of patients undergoing transcatheter aortic valve replacement. Abstract : Supplemental Digital Content is available in the text.